New Sequence Type ST3449 in Multidrug-Resistant Pseudomonas aeruginosa Isolates from a Cystic Fibrosis Patient - Catalina Díaz-Ríos; Marta Hernández; David Abad; Laura Álvarez-Montes; Athanasia Varsaki; David Iturbe; Jorge Calvo; Alain A. Ocampo-Sosa (Antibiotics, 2021)
Pseudomonas aeruginosa is one of the most critical bacterial pathogens associated with chronic infections in cystic fibrosis patients. Here we show the phenotypic and genotypic characterization of five consecutive multidrug-resistant isolates of P. aeruginosa collected during a month from a CF patient with end-stage lung disease and fatal outcome. The isolates exhibited distinct colony morphologies and pigmentation and differences in their capacity to produce biofilm and virulence potential evaluated in larvae of Galleria mellonella. Whole genome-sequencing showed that isolates belonged to a novel sequence type ST3449 and serotype O6. Analysis of their resistome demonstrated the presence of genes blaOXA-396, blaPAO, aph(3’)-IIb, catB, crpP and fosA and new mutations in chromosomal genes conferring resistance to different antipseudomonal antibiotics. Genes exoS, exoT, exoY, toxA, lasI, rhlI and tse1 were among the 220 virulence genes detected. The different phenotypic and genotypic features found reveal the adaptation of clone ST3449 to the CF lung environment by a number of mutations affecting genes related with biofilm formation, quorum sensing and antimicrobial resistance. Most of these mutations are commonly found in CF isolates, which may give us important clues for future development of new drug targets to combat P. aeruginosa chronic infections.